Hubungan antara Tingkat Pengetahuan PUS dengan Perilaku Pemeriksaan IVA - Yani, Dessy Inda; Susanti, Desy (Universitas Baiturrahim, 2025)
Cervical cancer is the second most common cancer that occurs in women caused by the Human Papilloma Virus (HPV). Prevention of cervical cancer can be done by early detection, one of which is by examining IVA (Visual Acetic Acid Inspection). IVA examination is an alternative examination because it is cheap, practical and high sensitivity. Factors that influence the behavior of PUS in carrying out IVA examinations is knowledge about cervical cancer. The level of knowledge of PUS about cervical cancer will have an impact on the low behavior of PUS in IVA examinations. This study aims to determine the relationship between PUS knowledge about cervical cancer and IVA examination behavior at the Klinik Sehat Keluarga Ceria. This type of research is quantitative with an analytic design with a cross sectional approach. The research sample is 75 respondents. The sampling technique used consecutive sampling and data analysis using Chi Square. The results of the statistical research showed that the level of knowledge of the respondents about cervical cancer was mostly in the fairly good category with 36 respondents (48%). the behavior of respondents who carried out the IVA examination was 21 respondents (28%). It was concluded that there was a relationship between knowledge of women of childbearing age about cervical cancer and IVA examination behavior at the Klinik Sehat Keluarga Ceria with a P value = 0.002 (P <0.05). The need to increase public knowledge about the importance of knowing about cervical cancer and the importance of early cervical cancer screening through community outreach. And more focused on PUS who have not undergone IVA examination and who have done it but not routinely.